ANALISIS NILAI-NILAI MORAL TRADISI ACCERA KALOMPOANG DI MUSEUM BALLA LOMPOA KABUPATEN GOWA - Mrs Fitriani; Rasmawati Sombuo; Aprian Early; Lukman Ilham (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2019)
This research was conducted to determine the moral values ​​of the accera kalompoang tradition carried out at the Balla Lompoa museum in Gowa district. The type of research used in this study is the type of qualitative research using a qualitative approach. The data in this research are the history of the birth and development of the accera kalompoang tradition, the ceremonial procession of the accera kalompoang tradition and the moral values ​​of the accera kalompoang tradition. The informants in this study were historians and culturalists of Gowa district, the royal family of Gowa, the management of the Balla Lompoa museum, the government and the local community who were involved and participated in the ceremony. The data collection method used in this study is the interview method and documentation. The results showed that the tradition of accera kalompoang existed since the reign of To Manurung Baineya, then continued by the 14th gowa king Sultan Alauddin by including Islamic nuances in it, monetized its implementation on the 10th of Dhulhijjah by the 14th king of Gowa, then this tradition was continued by his son king gowa the 15th Sultan of Malikussaid and during the reign of Sultan Hasanuddin the king of Gowa to the 16th this tradition was applied in an orderly manner both customarily and breathing Islam continuously and crystallized the way and shape to the king of Gowa who reigned until now. The process was carried out with various series of events which began with the allekka je’ne, Appidalleki, ammolong tedong program, and the washing of large objects starting with the allangiri, annyossorok and annimbang events. The results of the analysis of moral values ​​contained in this tradition are that this ceremony contains the value of glorification of the creator, respect for the ancestors, preserving cultural values, establishing friendship between noble families, the government and society, good cooperation, orderly rules and realizing tolerance and the existence of care for others.